TESTING THE IMPACT OF GROWTH STOCKS AND VALUE SHARES FOR DIVIDEND ADS THROUGH INFORMATIONAL CONTENT AND THEIR REFLECTION IN STOCK RETURNS (AN APPLIED STUDY IN THE IRAQ STOCK EXCHANGE FOR THE PERIOD 2016-2023) - Sajad Yousuf Khalif; Saad Majeed al-Janabi; Mohammed Faez Hasan (Scholars Digest Publishing, 2024)
This study aimed to show the announcement of dividends and the extent of its reflection in the returns of companies' shares and the role played by the information sent for these announcements in explaining the asymmetry of information for most companies to help investors obtain information that Increases the efficiency of the financial market in a semi-strong manner, and then make rational decisions through that information sent before and after the announcement of the dividends, The current study focuses on the type of shares owned by these companies (value-growth) In addition to testing the efficiency of the Iraqi stock market in a semi-strong manner, in order to address the gap due to the asymmetry of information between internal insiders (company managers) and external investors that enables investors to avoid losses in the future and don't make wrong decisions. The study sample consisted of twenty-nine companies listed on the Iraq Stock Exchange, which announced their dividends for the period from (1/1/2016 - 12/31/2023) with 101 advertisements, and a set of financial and statistical methods were used through the use of (SPSS) program for statistical analysis and testing of the hypotheses of the study, as well as the use of (Excel) program for financial analysis of the study variables, and the study reached a set of conclusions, the Most important of which is that the announcement of the dividend divider has an influential information content by achieving unusual and accumulated positive returns. And negative for the company before and after the announcement of the dividends divider for the companies of the study sample listed in the Iraq Stock Exchange and for all sectors, because if the announcement of the dividends did not have an influential information content, unusual returns would not have been achieved, whether positive or negative, and this means that there is a problem of information asymmetry, and this is reflected in the fact that the financial market is inefficient in an almost strong way.
Keywords: Growth stocks, Value stocks, Dividend announcements, Information content, Stock returns.